Combination of phosphodiesterase‐5‐inhibitors and beta blockers improves experimental portal hypertension and erectile dysfunction. (22nd July 2020) - Uschner, Frank E.; Glückert, Kathleen; Paternostro, Rafael; Gnad, Thorsten; Schierwagen, Robert; Mandorfer, Mattias; Magdaleno, Fernando; Ortiz, Cristina; Schwarzkopf, Katharina; Kamath, Patrick S.; Alessandria, Carlo; Boesecke, Christoph; et al.
Abstract: Background & Aims: Phosphodiesterase‐5 inhibitors (PDE‐5‐I) are used for treatment of erectile dysfunction (ED), which is common in patients with cirrhosis. They may improve portal hypertension (PH), but contradictory data on efficacy and side‐effects have been reported. Non‐selective beta blockers (NSBB) reduce portal pressure, but might aggravate ED. Thus, we evaluated the combination of PDE‐5‐I with NSBB and its impact on PH and ED in experimental cirrhosis. Methods: ED was assessed in cirrhotic patients (n = 86) using standardized questionnaire. Experimental cirrhosis was induced by bile‐duct‐ligation or carbon‐tetrachloride intoxication in rats. Corpus cavernosum pressure – a surrogate of ED ‐, as well as systemic and portal haemodynamics, were measured in vivo and in situ after acute administration of udenafil alone or in combination with propranolol. mRNA and protein levels of PDE‐5 signalling were analysed using PCR and western Blot. Results: ED in humans was related to severity of liver disease and to NSBB treatment. PDE‐5 was mainly expressed in hepatic stellate cells and upregulated in human and experimental cirrhosis. Propranolol reduced corpus cavernosum pressure in cirrhotic rats and it was restored by udenafil. Even though udenafil treatment improved PH, it led to a reduction of mean arterial pressure. The combination of udenafil and propranolol reduced portal pressure and hepatic resistance without systemic side‐effects. Conclusions: ED is common with advanced cirrhosis and concomitant NSBB treatment. The combination of PDE‐5‐I and NSBB improves ED and PH in experimental cirrhosis.